Comparative Study of Transmission and Control of HIV/AIDS in Pakistan (Bangladesh Journal of Medical Science, 2020)
Background: HIV/AIDS is nowadays considered as the greatest public health disaster of modern time. It has become the challenge for the global population for decades.Method: In our study, we shall emphasize on comparative study which coordinates the field of health awareness activities on the basis of educational and informational campaigns.Result: For this purpose we generate a mathematical model having two susceptible classes depending on changes in behavior with educational activities.Conclusion: We shall try to create stability between the numbers of infected individuals and the cost of the education campaign using optimal control theory.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.501-508